2001
DOI: 10.1016/s1011-1344(01)00118-x
|View full text |Cite
|
Sign up to set email alerts
|

Increase of the photosensitizing efficiency of the Bacteriochlorin a by liposome-incorporation

Abstract: To describe the action mechanisms of Bacteriochlorin a (BCA), a second generation photosensitizer, in phosphate buffer (PB) and in dimyristoyl phosphatidylcholine (DMPC) liposomes we carried out oxygen consumption and ESR measurements. In PB, where BCA was in a monomer-dimer equilibrium, our results suggested that the oxygen consumption was related to the BCA monomers concentration in solution. Incorporation of BCA in DMPC liposomes, by promoting the monomerization of BCA, increased 9-fold the oxygen consumpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(76 citation statements)
references
References 28 publications
(10 reference statements)
2
70
0
1
Order By: Relevance
“…3,4 Therefore, BCA is an attractive sensitizer since it has been demonstrated that BCA photosensitizes the production of 1 O 2 and that 1 O 2 is involved in killing cells in the presence of photoexcited BCA. 10, 12 Furthermore, oxygen consumption and electron paramagnetic resonance experiments seem to indicate that solubilization of BCA in the bilayers of DMPC liposomes leads to an increase of singlet oxygen production relative to the same value in phosphate buffer. This increase is concomitant with the monomerization of the dye.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3,4 Therefore, BCA is an attractive sensitizer since it has been demonstrated that BCA photosensitizes the production of 1 O 2 and that 1 O 2 is involved in killing cells in the presence of photoexcited BCA. 10, 12 Furthermore, oxygen consumption and electron paramagnetic resonance experiments seem to indicate that solubilization of BCA in the bilayers of DMPC liposomes leads to an increase of singlet oxygen production relative to the same value in phosphate buffer. This increase is concomitant with the monomerization of the dye.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, it has been shown that the survival of WiDr cells (derived from a primary adenocarcinoma of a rectosigmoid colon carcinoma) after PDT treatment was lower with a liposomal formulation of BCA than with treatment with BCA in cell culture medium. 12 Among the causes that could explain this effect, there are, of course, a higher singlet oxygen production but also other parameters like the modification of the cell uptake or location inside the cells when liposomes are used as drug carriers.…”
Section: Singlet Oxygen Production During Bca Irradiation In Phosphatmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, both phthalocyanines and chlorins are hydrophobic PSs that form aggregates in physiological solutions (16). When aggregated, the PSs are far less efficient in translating light energy into a chemical potential.…”
Section: Photosensitizer Liposome Formulationsmentioning
confidence: 99%
“…When aggregated, the PSs are far less efficient in translating light energy into a chemical potential. This happens because the effect of quenching is amplified in these aggregates, i.e., the aggregated molecule is not able to absorb light or, even though it absorbs light, the photoexcited PS decays to the ground-state before producing singlet oxygen (16). Moreover, PS aggregates also hamper parenteral administration (such as intravenous injection) and the delivery of the PS drugs to targeted tissues (6,7).…”
Section: Photosensitizer Liposome Formulationsmentioning
confidence: 99%